2019
DOI: 10.1016/j.arth.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty Reduces Pain and Improves Function in Patients With Spondyloepiphyseal Dysplasia: A Long-Term Outcome Study of 50 Cases

Abstract: Background: Spondyloepiphyseal dysplasia (SED) is rare genetic condition which leads to skeletal and joint deformities that can predispose patients to degenerative joint disease. There are limited reports on the results of total hip arthroplasty (THA) in this patient population. The purpose of this study is to review clinical and radiographic outcomes of THA performed in patients with SED at one institution. Methods: Among 43,917 patients undergoing primary THA from 1970 to 2015, we identified 50 THAs perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Based on relatively large cohorts reported by two groups, the average age at the time of total hip arthroplasty was under 40 years, i.e., 32 years in MED patients 19 ) and 39 years in SED patients. 20 ) In both groups, arthroplasty reduced pain and improved QoL in patients with skeletal dysplasia, but the quantitative outcomes were less marked than those reported after arthroplasty in patients without these skeletal dysplasias because of the high incidence of complications related to these conditions. To delay the onset of premature osteoarthritis, various osteotomies have been indicated for correcting deformities.…”
Section: Discussionmentioning
confidence: 88%
“…Based on relatively large cohorts reported by two groups, the average age at the time of total hip arthroplasty was under 40 years, i.e., 32 years in MED patients 19 ) and 39 years in SED patients. 20 ) In both groups, arthroplasty reduced pain and improved QoL in patients with skeletal dysplasia, but the quantitative outcomes were less marked than those reported after arthroplasty in patients without these skeletal dysplasias because of the high incidence of complications related to these conditions. To delay the onset of premature osteoarthritis, various osteotomies have been indicated for correcting deformities.…”
Section: Discussionmentioning
confidence: 88%
“…The progressing pathology of the hip in patients with SED renders arthroplasty an almost inevitable part of the treatment plan, at a time defined after regular follow-up. In a retrospective study 12 , THA demonstrated notable pain relief and functional improvement, leading to the majority of patients being able to walk independently post-surgery. However, patients with SED experienced a significant rate of complications while the mean age was 39 (16-79) years and 12 patients (24%) underwent at least 1 surgical intervention on the same hip.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 There are only few reports demonstrating significant pain reduction, improved function, and independent movement following total hip arthroplasty in patients with spondyloepiphyseal dysplasia. 3,9 Each type of skeletal dysplasia has its own unique pathological characteristics. However, none of the available studies evaluating total knee arthroplasty in multiple forms of skeletal dysplasia describe the surgical technique in patients with spondyloepiphyseal dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Abnormal bone and joint development, in conjunction with altered biomechanics, predisposes spondyloepiphyseal dysplasia patients toward the premature development of osteoarthritis, especially in hip and knee joints. 3 , 4 In the case of children, joint preservation techniques, including osteotomies to achieve an upper femur and sagittal spinopelvic radiographic alignment, are recommended to improve hip pain and range of motion. 5 However, alterations in development, anatomy, and biomechanics may require joint replacement surgery during the young adult age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation